2016
DOI: 10.1007/s10456-016-9521-x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific membrane antigen (PSMA)-mediated laminin proteolysis generates a pro-angiogenic peptide

Abstract: Prostate-specific membrane antigen (PSMA) is a membrane-bound glutamate carboxypeptidase expressed in a number of tissues. PSMA participates in various biological functions depending on the substrate available in the particular tissue; in the brain, PSMA cleaves the abundant neuropeptide N-acetyl-aspartyl-glutamate to regulate release of key neurotransmitters, while intestinal PSMA cleaves polyglutamated peptides to supply dietary folate. PSMA expression is also progressively upregulated in prostate cancer whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 56 publications
3
42
0
Order By: Relevance
“…We found that tumors in wild-type animals were larger and of higher grade with a higher microvessel density as compared to tumors in the PSMA knockout animals, which is consistent with our previous results implicating PSMA as an angiogenic regulator (36, 37, 42). In addition, PSMA-positive tumor cells were viable at greater distances from the vasculature than their PSMA knockout counterparts, suggesting that cell-intrinsic survival components also contribute to tumor growth.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that tumors in wild-type animals were larger and of higher grade with a higher microvessel density as compared to tumors in the PSMA knockout animals, which is consistent with our previous results implicating PSMA as an angiogenic regulator (36, 37, 42). In addition, PSMA-positive tumor cells were viable at greater distances from the vasculature than their PSMA knockout counterparts, suggesting that cell-intrinsic survival components also contribute to tumor growth.…”
Section: Introductionsupporting
confidence: 92%
“…We have previously shown that PSMA regulates angiogenesis by modulating integrin signal transduction and β 1 integrin–dependent FAK-Tyr 925 phosphorylation in endothelial cells (36, 37, 42) and show here that its expression alters FAK phosphorylation and IGF-1R signaling pathways in PCa cells (Fig. 6).…”
Section: Discussionsupporting
confidence: 65%
“…In a collaboration with Shapiro's research group on our knockout mouse model, we used an in vivo assay to evaluate activation of endothelial cell ingrowth (neovascularization) into an extracellular matrix plug (Matrigel; Corning). The PSMAknockout animals responded with dramatically attenuated vascular growth and reduced hemoglobin content, compared with the wild-type animals (39). Similarly, the PSMA inhibitor 2phosphonomethyl pentanedioic acid also blocked neovascularization.…”
Section: Role Of Psma In Tumor-associated Neovasculaturementioning
confidence: 87%
“…These assays have been instrumental in the study of vascular biology in growth and development [68] but also play a key role in the design, development, and evaluation of drugs that positively or negatively modulate vessel function for the treatment of many diseases [911]. Some examples of where the use of such bioassays has been imperative are: (1) the development of angiostatic drugs for the treatment of cancer, ocular diseases, and other pathologic conditions where angiogenesis is implicated and also angiogenic treatment strategies in ischemic cardiovascular disease [12, 13], (2) screening of natural anti-angiogenic compounds [14], (3) the efforts to design combination therapies including angiogenesis inhibitors [1520], (4) the unraveling of mechanisms regulating lymphangiogenesis [21, 22], (5) the interrelationship of angiogenesis and immunity [2325], (6) the development of imaging as diagnostic strategy [26], (7) the study of drug resistance mechanisms [2729], (8) development of compounds and strategies for the revascularization of ischemic injuries [30, 31], and (9) to improve the vascular fitness in aging vessels [32, 33]. The current paper describes a large collection of assays and techniques for the evaluation of angiogenesis and aims at explaining their respective advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%